Assays of the metabolic viability of single giant mitochondria. Experiments with intact and impaled mitochondria (The Rockefeller University Press, 1978)
Single giant mitochondria isolated from mice fed cuprizone were assayed for their metabolic viability. Two tests were devised. One test optically detected the accumulation of calcium phosphate within the mitochondria under massive loading conditions (including the presence of succinate and ATP). The accumulation corresponds to a test of energy coupling from either electron transport or the hydrolysis of ATP since it is blocked by either antimycin A or oligomycin. The other assay tested for the production of ATP from ADP and Pi, using myofibrils. Myofibrils prepared from glycerinated rabbit psoas muscle contract only in the presence of ATP and not in the presence of ADP. Myofibrillar contraction is unaffected by the presence of antimycin A or oligomycin. However, myofibrils in the presence of mitochondria that are phosphorylating ADP to ATP do contract. This contraction is blocked by antimycin A and/or oligomycin. Hence, the ATP which causes myofibrillar contraction is produced by oxidative phosphorylation. At low mitochondrial concentration, only the myofibrils in close proximity with mitochondria contract in the presence of ADP. Therefore the assay can be used to test the viability of individual mitochondria. Individual giant mitochondria were found to be viable, using both of these assays. Comparable results were obtained in mitochondria impaled with microelectrodes. The potentials and resistances were unaffected by concomitant calcium phosphate accumulation or oxidative phosphorylation.